STUDY OF REGENERATION POTENTIAL IN COMMON MILLET (PANICUM MILIACEUM L.) VARIETIES IN VITRO CULTURE - Zhumabek, A.T.; Sutula, M.Y.; Manabayeva, S.A. (Eurasian Journal of Applied Biotechnology, 2024)
In Kazakhstan, common millet (Panicum miliaceum L.) stands as a significant agricultural crop, annually cultivated over an area of approximately 17.5 thousand hectares. This study aimed to develop and optimize a simple and effective method for inducing callus formation and plant regeneration in millet. The research focused on exploring the regeneration potential of Kazakhstani varieties, Kormovoe-14 and Yarkoe-6. Seeds of millet were cultivated on modified Murashige and Skoog medium supplemented with Gamborg B5 vitamins and growth regulators, including 2 mg/L 2,4-D and 0.5 mg/L 6-BAP, to induce callusogenesis. Additionally, amino acids such as 500 mg/L L-proline and 300 mg/L casein hydrolysate were added to the medium to provide an additional nitrogen source. The induction frequency of callusogenesis averaged 95% for both Kormovoe-14 and Yarkoe-6 breeding lines. All examined varieties exhibited 100% induction of embryogenic callus when using MS medium supplemented with 2 g/L L-proline, 30 g/L maltose, 5 mg/L 2,4-D, and 1 mg/L BAP. Morphogenic, friable, and compact Type II calli with chlorophyll-containing zones were transferred to MS medium for regeneration, containing 4 mg/L BAP and 500 mg/L L-proline. The maximum number of shoots for both varieties was obtained on auxin-free MS medium containing 4 mg/L BAP, with a regeneration frequency of 47.5% (Kormovoe-14) and 37.5% (Yarkoe-6). Regenerated plants were transferred to full-strength MS medium supplemented with 0.2 mg/L IAA and 0.1 mg/L BAP, 2% sucrose, for rhizogenesis. Successfully rooted plantlets were adapted and transferred to soil. These findings lay the groundwork for the development of effective genetic transformation methods and the creation of transgenic proso millet plants.